Slow-Walk: Climate as Volatility and Expansive Political Practice. Issue 3 (20th December 2016) - Joseph, May
Abstract : A lone tree stands in the midst of a devastated landscape at Rikuzentakata, Japan. At Aceh, Malacca, a whole generation is washed out by the 2004 tsunami. At Beach 116, Far Rockaway, New York City, the entire street is swept away as the sea rolls in from the ocean toward the Jamaica Bay end of the avenue, built on a slope from ocean to bay on a barrier island. These scenes of climate volatility arouse in coastal communities a sense of vulnerability, of risk as a way of life. It is a daily choreography of uncertainty whose underlying structures shape the performance work of the movement-based theater company Harmattan Theater, which I started in 2009.